Computerized cognitive interventions for preventing dementia in people with mild cognitive impairment: A systematic review with meta‐analyses. (20th December 2022) - Zuschnegg, Julia; Schoberer, Daniela; Häussl, Alfred; Russegger, Silvia; Ploder, Karin; Fellner, Maria; Hofmarcher‐Holzhacker, Maria; Roller‐Wirnsberger, Regina; Paletta, Lucas; Koini, Marisa; Schüssler, Sandra
Abstract: Background: People with mild cognitive impairment (MCI) are faced with a higher risk of developing dementia, but with a "window of opportunity" for prevention and treatment. Computerized cognitive interventions (CCIs) might constitute a beneficial non‐pharmacological treatment approach. This systematic review evaluated evidence of CCIs performed individually with a computer, tablet‐PC, game consoles, virtual reality (VR), or augmented reality (AR) on cognition in community‐dwelling people with MCI. Method: A systematic review and meta‐analyses of randomized controlled trials (RCTs) was performed. The systematic literature search was conducted in MEDLINE, CINAHL, Embase, Cochrane CENTRAL, IEEE Xplore Digital Library, ISI Web of Knowledge, Scopus and PsycINFO, and included an additional search for gray literature. The search was completed by backward citation tracking. The methodological quality of the included RCTs was independently assessed by two reviewers. Comparable studies were pooled using the random‐effects model. Result: A total of 18 randomized controlled trials (RCTs) were identified. 12 RTCs were used for conducting meta‐analyses which showed significant effects of CCIs for people with MCI in memory (SMD 1.12, CI 95% [0.08, 2.16]), working memory (SMD 0.85, CI 95% [0.32, 1.38]), attention/concentration/processing speed (SMD 0.61, CI 95% [0.21, 1.02]), executive functioning (SMD 0.96, CI 95% [0.26, 1.66]), and language (SMD 1.63, CI 95% [0.20, 3.06]), but no significant improvement in global cognition. Pooling follow‐up evaluations was not possible, but one of two studies showed continuing significant differences for the intervention group after 6 months post intervention in memory and working memory. CCIs were conducted predominantly with computers, followed by tablet‐PCs, VR, AR, and mixed reality. Conclusion: This review demonstrated beneficial effects of CCIs on domain‐specific cognition in people with MCI. Therefore, CCIs might be a valuable treatment option to maintain cognition and prevent progression to dementia. However, further research is necessary, especially on CCIs applied with emerging technologies like VR or AR. Furthermore, various outcome measurements used in the studies were challenging for the pooling of study results, which highlights the need for a predefined set of important cognitive outcomes and tools for future RCTs.